Memaknai Suara Hati sebagai Model Politik Etis Kekristenan Humanis Meminimalisir Pengaruh Politik Identitas di Indonesia - Aziz, Budi Astra; Tarigan, Erikson; Ginting, Alemina Br (CV. Creative Tugu Pena, 2024)
Politics today has a negative connotation, and almost all crimes, violence and conflicts occur for political reasons. In Indonesia today, identity politics is getting stronger, especially politics using the issue of religious differences, all these symptoms and phenomena are fertile ground for the practice of dehumanisation, namely treating humans inhumanely. This must be addressed theologically to minimise the destructive impact due to the shallowing of the substance and function of politics itself in the life of plural Indonesian society. The author uses conscience as a theological locus in finding a model of Christian political ethics, becoming a theological contribution for Christianity to live out what kind of political model is in accordance with the Christian faith which is humanist in praxis and minimises the negative effects of identity politics. The goal is that Christianity can play politics in accordance with the ethical rules of its faith, and can be an example and role model for the wider community on how to play healthy and correct politics Keywords: Ethics, Conscience, Politics, Humanism and Identity Politics